A preliminary study of regional creative vision: insights from creative enterprises’ founders in Indonesia - Pratama, Andika Putra; Maryunani, Salfitrie Roos; Badriyah, Mila Jamilah Khatun; Hajarrahmah, Dini (Creativity Studies, 2024)
A creative enterprise (i.e. enterprise in the creative industries) can be understood as an enterprise that relies principally on the creativity of individuals engaged in it. Thus, creativity can be said to define the entire pursuit of creative enterprises. This paper highlights the motivational aspect of creativity in the notion of ‘creative vision’ based on interviews with founders of creative enterprises in three different regions in Indonesia (Bandung, Yogyakarta, and Bali), encompassing three creative sectors (cuisine, craft, and fashion). Three forms of creative vision have been discovered (collective self-actualization, collective altruism, and co-creation), with each form predominantly signifying each region sampled. Through a collaborative effort of sensemaking in the research team, the current preliminary study contributes to discourses about the nature of creativity or what it entails; it is derived not from the conscious understanding of what creativity is or means by experts and the likes, but from the actual vision of practitioners of creativity from the field where creativity is the soul. The findings emphasize how creativity can be defined: what does it mean to be creative?